Implementation of Augmented Reality-Based Pop-Up Books to Enhance Elementary Students’ Understanding of Ecosystem Concepts - Moch Bayu Ibrahim; Suwito Eko Pramono; Fakhruddin Fakhruddin; Bambang Subali (Universitas Negeri Semarang, 2025)
This study aims to implement and examine the effectiveness of an Augmented Reality (AR) based Pop-Up Book in enhancing elementary students’ understanding of ecosystem concepts. The research employed a One Group Pretest-Posttest Design, involving 139 fifth-grade students from five elementary schools in Surabaya City, Indonesia. The research instruments consisted of a concept comprehension test, observation sheets, and a student response questionnaire. Data were analyzed using a paired-sample t-test and the Normalized Gain (N-Gain) calculation. The findings revealed a significant improvement in students’ learning outcomes, with an average pretest score of 62 and posttest score of 89, resulting in an N-Gain of 0.70, which falls within the high category. Moreover, the classical mastery level reached 100%, and the student response rate toward the media was 98%, categorized as very positive. The AR-based Pop-Up Book proved to be effective in helping students comprehend ecosystem concepts, as it enables them to visualize interrelationships among organisms, energy flow, and biotic–abiotic components in a concrete, engaging, and interactive manner. Furthermore, this medium enhanced students’ motivation, participation, and engagement throughout the learning process. Hence, the AR-based Pop-Up Book can serve as an innovative, contextual, and effective science learning medium aligned with the characteristics of 21st century learners.